Sistem Nomor Antrian Bantuan Sosial di BRILink Berbasis Web Studi Kasus BRILink Mingalvo Desa Hutumuri, Ambon - Vitalona Crysantini Paays; Andreas Handojo; Djoni Haryadi Setiabudi (Jurnal Infra, 2022)
BRILink Mingalvo is located in Hutumuri Village, South Leitimur District, Ambon City. BRILink Mingalvo is a BRI agent that can assist the public in making withdrawal transactions, payments, and social assistance collection without the community having to go to BRI which is a long distance from where they live. At BRILink people who get social assistance must come first and queue to make transactions, of course this is inefficient and a waste of time for people who have to do other activities. Therefore, a queue application is required for social assistance collection on BRILink. An app that can be accessed by social assistance recipients wherever they are.This web-based application is created using the HTML, PHP, and MySQL database programming languages. The First create source code in sublime text 3, and continued by creating a database on MySQL. After the program is completed, Testing on users and admins for the application.The end result of the development of this application is that it can easily retrieve queue numbers, can view transactions in progress, and in the admin can add a social assistance retrieval schedule for the user.